Genomic study in Mexicans identifies a new locus for triglycerides and refines European lipid loci. Issue 5 (15th March 2013) - Weissglas-Volkov, Daphna; Aguilar-Salinas, Carlos A; Nikkola, Elina; Deere, Kerry A; Cruz-Bautista, Ivette; Arellano-Campos, Olimpia; Muñoz-Hernandez, Linda Liliana; Gomez-Munguia, Lizeth; Ordoñez-Sánchez, Maria Luisa; Reddy, Prasad M V Linga; Lusis, Aldons J; Matikainen, Niina; et al.
Abstract : Background: The Mexican population and others with Amerindian heritage exhibit a substantial predisposition to dyslipidemias and coronary heart disease. Yet, these populations remain underinvestigated by genomic studies, and to date, no genome-wide association (GWA) studies have been reported for lipids in these rapidly expanding populations. Methods and findings: We performed a two-stage GWA study for hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C) in Mexicans (n=4361), and identified a novel Mexican-specific genome-wide significant locus for serum triglycerides (TGs) near the Niemann–Pick type C1 protein gene (p=2.43×10 −08 ). Furthermore, three European loci for TGs (APOA5, GCKR and LPL), and four loci for HDL-C (ABCA1, CETP, LIPC and LOC55908) reached genome-wide significance in Mexicans. We used cross-ethnic mapping to narrow three European TG GWA loci, APOA5, MLXIPL, and CILP2 that were wide and contained multiple candidate variants in the European scan. At the APOA5 locus, this reduced the most likely susceptibility variants to one, rs964184. Importantly, our functional analysis demonstrated a direct link between rs964184 and postprandial serum apoAV protein levels, supporting rs964184 as the causative variant underlying the European and Mexican GWA signal. Overall, 52 of the 100 reported associations from European lipid GWA meta-analysis generalised to Mexicans. However, in 82 of the 100 European GWA loci, a different variant other than the European lead/best-proxy variant had the strongest regional evidence of association in Mexicans. Conclusions: This first Mexican GWA study of lipids identified a novel GWA locus for high TG levels; used the interpopulation heterogeneity to significantly restrict three previously known European GWA signals, and surveyed whether the European lipid GWA SNPs extend to the Mexican population.